Genetic variation and preliminary marker-trait associations for cane quality traits in a diverse world collection of sugarcane (Saccharum spp.) and wild relatives - Eltaher, Shamseldeen; DeStefano, Douglas; Abuasbeh, Yasmeen; Sandhu, Hardev S.; Rouse, Matthew; Ali, Gul Shad; Singh, Sukhwinder (Frontiers in Plant Science, 2025)
IntroductionModern sugarcane cultivars originate from a limited genetic pool, primarily comprising Saccharum spontaneum and S. officinarum, which restricts yield improvements and stress resilience. It's vital to conserve and utilize genetic diversity from the World Collection of Sugarcane and Related Grasses (WCSRG) and is a key resource for future advancements.MethodsThe Cane Presentation System measures essential parameters, including Brix, Polarity, moisture, and fiber content, which are critical for evaluating sugar extraction potential and processing efficiency. Molecular markers hold significant value in sugarcane breeding, and genome-wide association studies have been conducted to identify genetic loci associated with these target traits.ResultsThe study assessed variations in cane quality traits (Brix, polarity, fiber, and moisture content), finding that hybrids and S. robustum outperformed in these characters. Trait correlation analysis indicated independent genetic control, forming a basis for future research. Genome-wide association studies identified 40 significant SNPs across chromosomes 2 to 8, with markers on chromosomes 4, 6, and 7 consistently associated with Brix, and markers on chromosomes 2 and 5 linked to fiber. Additionally, marker AX-171243917-4651 on chromosome 6D was associated with both Brix and polarity.DiscussionThis study examines the genetic diversity and trait associations in sugarcane, emphasizing the application of stable SNP markers linked to key characteristics, such as Brix, Polarity, and fiber content, for enhancing multiple traits through marker-assisted selection. The findings reveal significant phenotypic variation among Saccharum species, advocating for a broad genetic base in breeding programs. Due to sugarcane's polyploid nature, the study calls for further validation through fine mapping, gene expression analysis, and multi-location testing. Future research should enhance marker density, expand populations, and adopt new genomic approaches for effective crop improvement.